The management of obstetrical hemorrhage - Taylor, Howard (2015)
The problem of obstetric hemorrhage is discussed on the basis of 56, 347 births to lying on the "Sloane Hospital for Women" of the Columbia Medical Center - Presbyterian. During this period there were 291 cases of placenta previa. In 2% of all the bleeding it exceeded 500 ml. In the last 10 years they have been observed and treated 101 cases Hypofibrinogenemia, for which intravenous administration of 3 to 6 grams of fibrinogen is advised.